2022
DOI: 10.5455/medarh.2022.76.55-61
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Treating Tibial Shaft Fractures Using Intramedullary Nailing (IMN) versus Minimally Invasive Percutaneous Plate Osteosynthesis (MIPPO)

Abstract: Background: Tibia shaft fractures are one of the most common long-bone fractures, second most common open sport-related injuries and they are estimated to occur in 4 percent of the senior population. Objective: Management of tibial fractures has been updating to achieve the best outcomes and avoid complications especially when talking about most common long bone fractures. Less invasive fixation techniques are the preferred ones to reduce surrounding soft tissue injury,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 41 publications
0
8
0
3
Order By: Relevance
“…Unlike IMN, MIPO does not damage the penetrating blood vessels and nutrient vessels of the broken bones, which ensures sufficient blood supply for osteogenesis and the growth pathway of osteoid to cartilage scab under low oxygen tension, providing a good growth environment for fracture healing, thus favouring fracture healing 16 . Studies have also found that MIPO provides a better healing environment when treating tibial shaft fractures 57 . Therefore, MIPO is superior to IMN in promoting wound healing.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike IMN, MIPO does not damage the penetrating blood vessels and nutrient vessels of the broken bones, which ensures sufficient blood supply for osteogenesis and the growth pathway of osteoid to cartilage scab under low oxygen tension, providing a good growth environment for fracture healing, thus favouring fracture healing 16 . Studies have also found that MIPO provides a better healing environment when treating tibial shaft fractures 57 . Therefore, MIPO is superior to IMN in promoting wound healing.…”
Section: Discussionmentioning
confidence: 99%
“…Несмотря на улучшение технологии хирургических методов лечениятребуется, при переломах большеберцовой кости могут встречаться случаи замедленного костного сращения и неудовлетворительных результатов. Конечно, результаты лечения зависят как от характера перелома, так и от метода лечения [14][15][16][17].…”
Section: оригинальные статьиunclassified
“…При накостном остеосинтезе обычно требуется большой по протяжённости оперативный доступ, что приводит к увеличению кровопотери и дополнительной травматизации окружающих перелом мягких тканей, а, следовательно, к ухудшению кровоснабжения зоны перелома [14][15][16]. Основным недостатком интрамедуллярного остеосинтеза является значительное Гений ортопедии.…”
Section: оригинальные статьиunclassified
“…During MIPPO, an incision of approximately 3 cm in length was made at one end of the fracture, and then a steel plate was inserted percutaneously; after the force line and alignment of the fracture were restored, the screw was inserted percutaneously for fixation. Generally, MIPPO does not require cutting the fracture end, so it can maximize the preservation of blood supply to the fracture and is conducive to fracture healing [ 2 , 3 ]. Some scholars believe that MIPPO is suitable for treating comminuted fractures with lots of bone fragments, numerous cancellous bones and a large contact surface [ 4 ].…”
Section: Introductionmentioning
confidence: 99%